Ablation Difficulty Score: Proposal of a new tool to predict success rate of percutaneous ablation for hepatocarcinoma. Issue 146 (January 2022) - Conci, Simone; D'Onofrio, Mirko; Bianco, Andrea; Campagnaro, Tommaso; Martone, Enrico; De Bellis, Mario; Longo, Chiara; Dedoni, Sara; Vittoria D'Addetta, Maria; Ciangherotti, Andrea; Pedrazzani, Corrado; Dalbeni, Andrea; et al.
Abstract: Purpose: Identify the factors related to failure ablation after percutaneous ultrasound guided single electrode radiofrequency ablation (RFA) for hepatocarcinoma (HCC) and propose a score for improving patient selection and treatment allocation. Methods: From 2010 to 2020 585 HCC nodules treated with RFA were prospectively collected. Ablation Difficulty Score (ADS) was built-up according to clinical and radiological factors related to failure ablation identified by Cox-logistic regression analysis. The study population was stratified in low risk (ADS 0), intermediate risk (ADS 1), and high risk (ADS ≥ 2) of failure ablation. Results: Overall ablation success rate was 85.5%. Morbidity and mortality rates were 3.5% and 0.0%. According to per nodule analysis the following factors resulted related to failure ablation: size > 20 mm (p = 0.002), sub-capsular location (p = 0.008), perivascular location (p = 0.024), isoechoic appearance (p = 0.008), and non-cirrhotic liver (p = 0.009). The ablation success rate was 93.5% in ADS 0, 85.8% in ADS 1 and 71.3% in ADS ≥ 2 (p < 0.001). The 1-year local tumor progression (LTP) free survival was 90.2% in ADS 0, 80.6% in ADS 1, and 72.3% in ADS ≥ 2 (p = 0.009). Nodule's size > 20 mm (p = 0.014), isoechoic appearance (p = 0.012), perivascular location (p = 0.012) resulted related to lower LTP free survival. Conclusion: Ablation Difficulty Score could be a simple and useful tool for guiding the treatment decision making of HCC. RFA in high risk nodules (ADS ≥ 2) should be carefully evaluated and reserved for patients not suitable for surgery or liver transplantation.